PEMAHAMAN KONFLIK BATIN TOKOH DALAM NOVEL RONGGENG DUKUH PARUK KARYA AHMAD TOHARI - Ramlah, Ramlah (BAHASANTODEA, 2015)
This research was motivated by a desire to find psychological conflict of the main character in the novel Ronggeng Dukuh Paruk written by Ahmad Tohari. This research aimed to describe the psychological conflict of the main character in the novel Ronggeng Dukuh Paruk, by Ahmad Tohari with psikoanalisis Sigmund Freudâ€™s theory that divided the human personality into there, namely the id, ego, and superego in the attitude of repression, sublimation, rationalization, aggression, projection, diversion, apathy and fantasy. This research was a qualitative research, being descriptive, using textual approaches and literature technigues. Analysis and interactive models by Miles and Huberman done by marking,classify, and coclude the results of analysis that is consistent with the of Sigmund Freudâ€™s personality theory. Pengeran displayed Rasus character as the narrator in novel Ronggeng Dukuh Paruk Hamlet was being displayed as a character who told Rasus. The main conflict deeloved in chapter there, namely when Srintil completed the last reguirement mus be a ronggeng. The requirement that must be fulfilled was named â€œbukak-klambuâ€. A requirement that destabilize the relationship between Rasus end Srintil. The results showed that in a natural psychiatric conflict was experienced by Srintil figure wit himself happened because Â Srintil psychiatric conflict by herself occurred as the result of Rasusâ€™s refusal to bicome her husband and leaved her, and Srintil psychiatric conflict with the surrounding occurred when Srintil was involved by the communist minions and must be entered into the prison and She was be disappointed by Bajus because selling her to Pak Blengur. The peak of the problem occurred when Srintil has became a Ronggeng Dukuh Paruk. Srintil belonged to the people and Rasus as a man who loved her, should let her. Keywords: Conflict Psychiatric, Psychoanalysis, Ronggeng Dukuh Paruk.